DESIGN OF ACADEMIC ORGANIZATION PERFORMANCE MEASUREMENT SYSTEM - Edy Susanto; Ahmadi Ahmadi; Benny Sukandari (JOURNAL ASRO, 2019)
The Naval Academy must spur its potential to be able to compete with other tertiary institutions. To make it happen certainly need a good improvement. The Navy Academy's performance evaluation system in terms of operational and administrative aspects is not optimal. Based on the planned improvement of the Naval Academy which is compiled annually it is still needed. The report on the implementation of work programs and budgets at the end of the year is not yet sufficient to measure the actual performance of the Navy Academy, by the required assessment system that can be used by management to improve performance and performance at the Navy Academy. The results of this evaluation are very important for the planning and determination of strategic steps and strategies to achieve the vision, mission and coordination objectives. Research Methods that Support Performance Measurement Systems using the Balanced Scorecard method. The design of a performance appraisal system that is in accordance with the concept of the Balanced Scorecard in this study used 8 strategic objectives as a criterion for evaluating the performance of tertiary institutions consisting of 27 KPIs.Keywords: Performance Measurement, Framework, Balanced Scorecard.